Signal Processing of Control and Protection for Traction ConverterBased on Butterworth Filter - ZHENG Yong; HUANG Qing; LI Xueming (机车电传动)
Aiming at the problems of electric locomotive traction converters affected by the bad application environment andthe control strategy, which brought high frequency harmonic for sampling signal of control and protection and affected the controlperformance and judgment of protection actions, and considering the characteristics of Butterworth low-pass filter, such as maximally flatamplitude-frequency response and good linear phase, as well as the advantages of simple structure and easy to design, a kind of tractionconverters signal processing method based on Butterworth low-pass filter was studied, and the design principle of Butterworth low-passfilter was introduced in detail. The experimental results showed that the designed Butterworth low-pass filter could effectively filter outhigh-frequency signal of traction converter.